Sistem Pendukung Keputusan Penentuan Barista Terbaik Menggunakan Rank Sum dan Additive Ratio Assessment (ARAS) - Sanriomi Sintaro (PT. SNN MEDIA TECH PRESS, 2023)
The selection of the best barista has become a crucial factor in guaranteeing a unique and satisfying coffee experience for connoisseurs. As an appreciation of the art of coffee making increases, barista selection no longer revolves around technical skills, but also on creativity, dedication, and interpersonal expertise. This study aims to apply the ARAS (Additive Ratio Assessment) method in determining the best barista using the Rank Sum weighting method, so that the results of the criteria weighting will be better in producing the best barista recommendations based on the decision support system model. The criteria used in selecting the best barista are barista skills, barista knowledge, experience, mastery of tools, and communication. Based on the ranking results using the ARAS method, it recommended rank 1 with a final value of 0.9483 obtained by Fandy, rank 2 with a final value of 0.9294 obtained by Abdur, and rank 3 with a final value of 0.8902 obtained by Delvin. The results of the test assessment using the blackbox testing model all the features of the best barista determination application are in accordance with their functions, the final results of application testing by 100% have worked according to the features made.